Challenge, Planning, Execution: The Seaward Defence of the Assault Area off Normandy, 6-14 June 1944 - Whitby, Michael (The Northern Mariner / Le marin du nord, 2025)
This study focusses on the nighttime defence of the American and British assault anchorages off Normandy from enemy surface attack in the period 6-14 June 1944. The subject is typically glossed over. Yet, the defence of the assault areas, like every other aspect of Operation NEPTUNE, was taken seriously by planners. Although German surface forces were not powerful enough to defeat the assault or make the anchorage untenable, if they were able to penetrate the assault area to sink vulnerable transports and landing craft with any regularity, they could disrupt the critical build-up of men and materiel into Normandy and impede the progress of the ground war. Further, rather than being a “one-off” defensive scheme for a massive assault unlikely to be repeated, elements of NEPTUNE’s defensive challenges may have been considered had the Allies been forced to invade Japan in late 1945. Its lessons, therefore, carried some weight.